Distribution of improved varieties of cassava and potential impact on root yield and disease reduction in Nigeria - Okechukwu, R.U.; Kehinde, I.A.; Afolabi, C.; James, B.; Egesi, Chiedozie N. (2011)
Eleven improved varieties project were multiplied in 2009 by primary producers associated with the USAID/ IITA project Unleashing the Power of Cassava in Africa in response to the Food Price Crisis (UPoCA) in seven States of Nigeria. In 2010, stems from these multiplication farms were distributed to farmers in these States. Prior to the distribution exercise a baseline survey was conducted on 630 farm families to ascertain among other issues their perception of cassava mosaic disease and other cassava pests. At the end of the harvest 2010 planting season, a survey of a subset of the recipients (80 villages) showed that the farmers are better informed and are replacing local varieties with improved varieties but would still need more extension service support on the best time to harvest these varieties to minimize losses due to rot.